COMPARISON OF SERUM BILIRUBIN ESTIMATION WITH TRANSCUTANEOUS BILIRUBINOMETRY IN NEONATES: Serum Bilirubins versus Transcutaneous Bilirubinometry - Waqar, Maj Talal; Ahmad, Zeeshan; Ali, Salman (Pakistan Armed Forces Medical Journal, 2010)
Objective: To assess usefulness of Minolta Airshield transcutaneous bilirubinometer by comparing bilirubin values obtained by transcutaneous jaundice meter with serum bilirubin estimation. Design: Analytical crosssectional study. Place and duration: NICU Military Hospital Rawalpindi Pakistan Jun 2002 to May 2005. Subjects and Methods: One hundred and fifty neonates admitted to NICU because of visible jaundice were included in the study. Serum was sent to laboratory for total bilirubin estimation. At the same time bilirubin was also checked by a Jaundice Meter. Data was tabulated and t-test applied to compare the two values. Results: One hundred and fifty paired estimations were performed. The transcutaneous bilirubin values ranged from 8.0 mg/dl to 20.4 mg/dl. While serum bilirubin by jaundice meter values ranged between 5.3 mg/dl and 26.0 mg/dl. A Scatter diagram was plotted. It showed a correlation coefficient of 0.78. Conclusion: Bilirubin values obtained by transcutaneous bilirubin meter were not significantly different from laboratory values thus proving the fact that transcutaneous bilirubinometer is a useful device to measure bilirubin.